Leverage and the Cost of Capital: Some Tests Using Nepalese Data - Khadka, Hari Bahadur (Journal of Nepalese Business Studies, 2007)
This paper is devoted to test the MM’s propositions about the relationship between leverage and cost of capital in the context of Nepalese capital markets. The main objective of the study is to determine whether the firms' overall cost of capital and cost of equity decline with the increasing use of leverage. The results showed a negative but insignificant beta value of the relationship between leverage and the overall cost of capital. Therefore the leverage may not be regarded as contributing variable to the cost of capital function for Nepalese firms. But finding contradicts with the traditional approach of the capital structure theories. It is further concluded that the cost of capital declines not only with leverage because of the tax deductibility feature of interest charge. The relationship between the cost of equity and leverage is also strongly negative. Besides leverage, the size, and D-P Ratio are other important variables that affect the cost of capital in Nepalese context. Journal of Nepalese Business Studies 2006/III/1 pp. 85-91